MAKNA SIMBOL BENTUK BANGUNAN ARSITEKTUR (MUSEUM PURNA BHAKTI PERTIWI) - Suryana, Fajar; Muktiono, Ayub (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2022)
A museum is a storage place for historical objects, and works of art that have other educational values, the architectural concept in the Museum building adapts from philosophy or environmental conditions to semiotic architecture, Semiotic architecture which is an architectural theory used to determine the meaning to be conveyed in architectural works. Meaning in architecture itself is divided into connotative meanings and denotative meanings. It can be interpreted that an architectural work is the same as a work of art in which it contains the meaning conveyed. So that the theory of semiotic architecture is very suitable to be used as an approach used in designing buildings that accommodate artistic activities and creativity. Creative meaning means having creativity, which is human nature that encourages people to discover new things. Creativity comes from intangible ideas and ideas that are developed and produced into something that we can feel, feel, see and enjoy. At this stage, creativity has become a product. Carrying the concept of